Estudo analítico e experimental do fenômeno de flutter em válvulas cardíacas prostéticas biológicas - Artur Henrique de Freitas Avelar (2016)
Cardiac valves regulate blood flow in the heart by maintaining the circulation in a single direction. When these valves have a disability, it can lead to serious heart problems; being responsible for 30% of cardiac surgery in adults and 80% of cardiac surgery in children in Brazil. As there isn't an ideal substitute for valves, there is a constant search for improvement of these prostheses since they began to be employed in the 50s. Biological tissue valves have the disadvantage of suffering from calcification and structural failure problems, with a service life of about 10 to 15 years. One phenomenon that may occur is an oscillation of the leaflets, known as flutter, which is associated with implications such as hemolysis, calcification, and fatigue. Although it is important and influences the life of bioprostheses, there are few studies in the literature that study methodically the causes and consequences of flutter and how to reduce or avoid its damage. Due to the importance of this problem for the industry and for the health of millions of patients who undergo the procedure of exchange of valves, it was decided to take this opportunity to contribute with an original study that collaborate to elucidate the phenomena involved in flutter and propose possible solutions. An analytical theory was proposed to predict the onset of oscillations and analyze the sensitivity of the variables as to their role in flutter. In conjunction, tests were performed in an experimental bench in order to quantify the frequencies and amplitudes of vibrations and make a dimensionless analysis that can be used to understand the behavior of prosthetic valve in its critical speed of onset of oscillations. The quantification of the phenomenon found frequencies over a wide interval of values ranging from 20 to 430 Hz and amplitudes varied from 0.1 to 2.5 mm. The analytical study was able to demonstrate how the dimensions of internal diameter and thickness have significant importance in the critical velocity of flutter, besides demonstrating the possibility of combining parameters to optimize the resistance of valves to the beginning of the oscillations. In addition, analytical and experimental study agree that the bovine pericardium valve is less susceptible to flutter, having superior performance to the porcine valve. In conclusion, the work made a thorough study of flutter phenomenon in biological prosthetic heart valves and made important contributions to the ultimate goal of creating an ideal artificial valve.